Peripheral T-Cell Reactivity to Heat Shock Protein 70 and Its Cofactor GrpE from Tropheryma whipplei Is Reduced in Patients with Classical Whipple's Disease - Trotta, Lucia (Infect Immun, 2017)
Classical Whipple's disease (CWD) is characterized by the lack of specific Th1 response toward Tropheryma whipplei in genetically predisposed individuals. The cofactor GrpE of heat shock protein 70 (Hsp70) from T. whipplei was previously identified as a B-cell antigen. We tested the capacity of Hsp70 and GrpE to elicit specific proinflammatory T-cell responses. Peripheral mononuclear cells from CWD patients and healthy donors were stimulated with T. whipplei lysate or recombinant GrpE or Hsp70 before levels of CD40L, CD69, perforin, granzyme B, CD107a, and gamma interferon (IFN-γ) were determined in T cells by flow cytometry. Upon stimulation with total bacterial lysate or recombinant GrpE or Hsp70 of T. whipplei, the proportions of activated effector CD4(+) T cells, determined as CD40L(+) IFN-γ(+), were significantly lower in patients with CWD than in healthy controls; CD8(+) T cells of untreated CWD patients revealed an enhanced activation toward unspecific stimulation and T. whipplei-specific degranulation, although CD69(+) IFN-γ(+) CD8(+) T cells were reduced upon stimulation with T. whipplei lysate and recombinant T. whipplei-derived proteins. Hsp70 and its cofactor GrpE are immunogenic in healthy individuals, eliciting effective responses against T. whipplei to control bacterial spreading. The lack of specific T-cell responses against these T. whipplei-derived proteins may contribute to the pathogenesis of CWD.